A rare case of median cleft of lower lip in Goldenhar syndrome - Khai Luen Koh; M Abd Latib (Wolters Kluwer Medknow Publications, 2018)
Median cleft on the lower lip (Tessier 30 cleft) is extremely rare with <100 cases reported in literature. Association with other craniofacial anomalies is known to occur, but some combination is extremely rare. We report a unique case of Tessier 30 cleft in a child with constellations of craniofacial cleft associated with Goldenhar syndrome. Rare facial clefts combinations reinforce the embryological basis that they are likely to result from disruption in migration of neural crest cells from rhombomeres to branchial arches rather than other simplistic theories. Case presented is distinct which will contribute to the current literature on rare craniofacial clefts syndrome.